(untitled) (Journal of actual problems of jurisprudence, 2022)
In modern Kazakhstani society, there is a high level of conflict, which is typical for legal disputes. In this regard, the resolution of disputes through traditional adversarial justice will further aggravate legal conflicts and lead to a complete termination of relations between the parties. Today, problems in the state judicial system lead to significant losses of material and moral benefits. As a result, one of the parties may be dissatisfied with the court decision, which may further complicate the enforcement of the court decision. Due to these circumstances, it is possible to turn to the institution of mediation, which is a relatively new legal institution. Mediation is an alternative dispute resolution (ADR) with the participation of a third party - an intermediary who is neutral, does not represent the interests of the parties in resolving the dispute, helps the parties to reach an agreement on the dispute, and the parties have full control over the decision-making process. The article discusses the development of the institution of mediation in Kazakhstan as an alternative method of dispute resolution. The reasons for the underdevelopment of the institution of mediation are analyzed, the opinions of legal scholars are analyzed, and the factors hindering the development of mediation in Kazakhstan are identified by comparing the experience of China, Germany, Georgia, Singapore in the implementation and development of alternative dispute resolution. In order to analyze these facts, a review and comparative analysis of the scientific works of scientists studying the Institute of Mediation and the laws and scientific works of a number of foreign countries on mediation was made. Based on the results of a sociological survey conducted by the Kazakhstan Institute for Strategic Studies under the President of the Republic of Kazakhstan about what Kazakhstanis know about mediation. The methodological basis of the article is the methods of analysis, synthesis, comparative legal, logical and legal, historical, statistical. Keywords: institution of mediation, mediator, alternative dispute resolution methods, mediation procedure, disputes, voluntariness, confidentiality.